Increasing tobacco cessation counseling and referral in a statewide oncology collaborative. Issue 28 (1st October 2022) - Ruiz Martinez, Mariem; Griggs, Jennifer J.; Liu, Manlan; DeVries, Kelly
Abstract : 327 Background: Oncology providers are uniquely positioned to provide tobacco cessation interventions because the motivation to quit can increase at the time of a cancer diagnosis. Physician advice to quit smoking increases the likelihood of a quit attempt by 25%. The Michigan Oncology Quality Consortium (MOQC), a physician-led quality improvement consortium of nearly all oncology practices in Michigan, has made tobacco cessation counseling and referral a priority. Methods: The Michigan Oncology Quality Consortium (MOQC) began abstracting tobacco cessation counseling and referrals from oncology medical records into the Quality Improvement Practice Initiative (QOPI) platform of the American Society of Clinical Oncology (ASCO) beginning in 2014. MOQC has developed and disseminated effective resources to ensure that practices in the consortium have access to tobacco cessation services through a grant to the Michigan Department of Health and Human Services (MDHHS). In 2017, performance on this measure was selected as one of our value-based reimbursement (VBR) measures. We also compared our data with responses from the Behavioral Risk Factor Surveillance System (BRFSS) obtained through MDHHS in response to the following question: "Earlier you indicated that you currently smoke cigarettes. Has your doctor or other health professional ever advised you of, or referred you to, a program or other resources available to help you stop smoking?". Results: Between 2015 and 2021, 6, 048 patients were included in the measure denominator. In 2015, only 44% of patients had documented counseling or referral to tobacco cessation services. Performance on this measure has increased each year as shown in the table. Data from the BRFSS Michigan Department of Health and Human Services (MDHHS) also show year-over-year improvement in patient reports of having been advised to quit. Conclusions: Our statewide collaborative successfully increased the proportion of patients who smoke who were either counseled to quit smoking or who were referred to smoking cessation services. The decrease in performance in 2020 and 2021 was likely to be the result of the COVID-19 pandemic. The addition of the VBR may have contributed to the success of our program. Through a partnership with HBOM- Health Behavior Optimization for Michigan, MOQC will create additional measures to continue to incentivize practices to get back to pre-pandemic levels of tobacco cessation referrals.Performance on this measure decreased in 2020 and in 2021. Year MOQC Performance P Value Michigan BRFSS Data P Value 2015 44% < 0.001 71% < 0.001 2016 52% 80% 2017 56% 77% 2018 64% 76% 2019 73% 79% 2020 65% 77% 2021 64% MOQC, Michigan Oncology Quality Consortium; MDHHS, Michigan Department of Health and Human Services Behavioral Risk Factor Surveillance System data.